View on Moscow from the Vorob'evye Hills, where Gercen and Ogarjow swore an oath to dedicate their lives to the liberation of the Russian people. From: Bro 587/1 fol, nr.6
View on Moscow from the Vorob'evye Hills, where Gercen and Ogarjow swore an oath to dedicate their lives to the liberation of the Russian people. From: Bro 587/1 fol, nr.6.